Financial sovereignty as one of Russia’s strategic objectives at the present stage - G. A. Chmut (Вестник университета)
Ensuring the financial sovereignty of the country is one of the key tasks to achieve national goals by 2030. The financial system of the Russian Federation (hereinafter referred to as Russia, RF) should do everything necessary to guarantee the financing of those needs that had been previously funded by Western countries. To do this, the inflow of long-term savings and investments in fast-growing high-tech projects is to be provided. President of RF during the meeting with members of the Government of Russia on January 11, 2023 noted the main directions of the Government’s work for 2023. One of the directions is strengthening the financial sovereignty of the RF which is a condition to increase investments in the country’s economy. M. V. Mishustin, Prime Minister of Russia, speaking with the Government’s report in the State Duma of Russia, mentioned that to achieve the financial sovereignty of the state is one of the important tasks for the current year. Attracting long-term financial resources to the economy, investment attractiveness and providing financial support for fast-growing technology companies are the main conditions to solve this problem. Thus, the Government of RF have developed five main directions for the task implementation in order to fulfill the instructions of President of RF.   The purpose of this article is to consider the main measures aimed at achieving financial sovereignty in the current conditions.   The activities of the Government of RF and the Bank of Russia on the implementation of the discussed mea sures are analysed as the results of the study. The main conclusion of the article is the justification of financial sovereignty role in increasing the prestige of the Russian economy.